Tula Virus Infections in the Eurasian Water Vole in Central Europe - Schlegel, Matthias; Kindler, E.; Essbauer, S.S.; Wolf, R.; Thiel, J.; Groschup, Martin H.; Heckel, G.; Oehme, R.M.; Ulrich, Rainer G. (Vector-Borne and Zoonotic Diseases, 2012)
Recent reports of novel hantaviruses in shrews and moles and the detection of rodent-borne hantaviruses in different rodent species raise important questions about their host range and specificity, evolution, and host adaptation. Tula virus (TULV), a European hantavirus, is believed to be slightly or non-pathogenic in humans and was initially detected in the common vole Microtus arvalis, the East European vole M. levis (formerly rossiaemeridionalis), and subsequently in other Microtus species. Here we report the first multiple RT-PCR detection and sequence analyses of TULV in the Eurasian water vole Arvicola amphibius from different regions in Germany and Switzerland. Additional novel TULV S-, M-, and L-segment sequences were obtained from M. arvalis and M. agrestis trapped in Germany at sites close to trapping sites of TULV-RT-PCR-positive water voles. Serological investigations using a recombinant TULV nucleocapsid protein revealed the presence of TULV-reactive antibodies in RT-PCR-positive and a few RT-PCR-negative water voles. Phylogenetic analyses revealed a geographical clustering of the novel S-, M-, and L-segment sequences from A. amphibius with those of M. arvalis- and M. agrestis-derived TULV lineages, and may suggest multiple TULV spillover or a potential host switch to A. amphibius. Future longitudinal studies of sympatric Microtus and Arvicola populations and experimental infection studies have to prove the potential of A. amphibius as an additional TULV reservoir host.